2011
DOI: 10.1111/j.1365-2613.2011.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of the liver in obese and diabetic ob/ob and db/db mice fed a standard or high-calorie diet

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the commonest liver diseases in Western countries. Although leptin deficient ob/ob and db/db mice are frequently used as murine models of NAFLD, an exhaustive characterization of their hepatic lesions has not been reported to date, particularly under calorie overconsumption. Thus, liver lesions were characterized in 78 ob/ob and db/db mice fed either a standard or high-calorie (HC) diet, for one or three months. Steatosis, necroinflammation, apoptosis and fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
100
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 42 publications
11
100
2
Order By: Relevance
“…In animal models, the presence or absence (and relevance) of hepatocyte ballooning is debated. It has been previously observed in mice and toxin-induced rat models of NASH (9,18), and in a recent elegant swine model of NASH (23); however, in our hands, as in others, the criteria according to the pathologist for ballooning were not met by simple but routine histochemical staining, agreeing with previous pathological examinations (40). A more detailed examination of hepatocyte ballooning, for example via K8/K18 immunostaining of liver sections, would be warranted to confirm this observation.…”
Section: Discussionsupporting
confidence: 89%
“…In animal models, the presence or absence (and relevance) of hepatocyte ballooning is debated. It has been previously observed in mice and toxin-induced rat models of NASH (9,18), and in a recent elegant swine model of NASH (23); however, in our hands, as in others, the criteria according to the pathologist for ballooning were not met by simple but routine histochemical staining, agreeing with previous pathological examinations (40). A more detailed examination of hepatocyte ballooning, for example via K8/K18 immunostaining of liver sections, would be warranted to confirm this observation.…”
Section: Discussionsupporting
confidence: 89%
“…One of the major advantages of these genetic murine models of obesity is the rapid and consistent occurrence of insulin resistance, hyperglycemia, and NAFLD (Lindström, 2007;Trak-Smayra et al, 2011;Massart et al, 2012), whereas high-fat diet-induced obesity is not always associated with these secondary metabolic disorders, even after several months of feeding (Burcelin et al, 2002;Begriche et al, 2008a). It is noteworthy that both ob/ob and db/db mice are characterized by "borderline NASH," because fatty liver is associated with moderate hepatic necroinflammation and mild fibrosis Begriche et al, 2008b;Trak-Smayra et al, 2011). Moreover, this study and previous investigations (Trak-Smayra et al, 2011) showed comparable basal levels of plasma transaminases between ob/ob and db/db mice, indicating a similar degree of hepatic cytolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several predisposing factors could enhance the risk and the severity of APAP-induced acute liver failure, including malnutrition, alcoholic liver disease, hepatitis C virus infection, and nonalcoholic fatty liver disease (NAFLD), which is often associated with obesity and type 2 diabetes (Nguyen et al, 2008;Myers and Shaheen, 2009). NAFLD encompasses a large spectrum of liver lesions such as fatty liver, nonalcoholic steatohepatitis (NASH), and cirrhosis (Diehl, 2002;Trak-Smayra et al, 2011). It is noteworthy that hepatic CYP2E1 activity is frequently enhanced in obese individuals with NAFLD (Chalasani et al, 2003;Aubert et al, 2011) and in type 2 diabetics (Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…mild fibrosis (44)(45)(46)(47). We analyzed the hepatocyte ploidy profile by flow cytometry (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI73957DS1).…”
Section: Introductionmentioning
confidence: 99%